Exclusive Breastfeeding among Canadian Inuit: Results from the Nunavut Inuit Child Health Survey. (May 2014) - McIsaac, Kathryn E.; Lou, Wendy; Sellen, Daniel; Young, T. Kue
Background: Very little population-based research has been conducted around the exclusive breastfeeding practices of Inuit Canadians. Objectives: This research aims to assess the distribution of exclusive breastfeeding among Inuit Canadians and to identify factors associated with exclusive breastfeeding as recommended. Methods: We use data from 188 infant-mother dyads who completed the Nunavut Inuit Child Health Survey, a cross-sectional, population-based survey of Inuit children aged 3 to 5 years. A series of multinomial logistic regression models were run to identify factors associated with 4 exclusive breastfeeding durations (≤ 1 month, > 1-< 5.5 months, 5.5-6.5 months, and > 6.5 months). Results: Of infants, 23% were exclusively breastfed as recommended (ie, between 5.5 and 6.5 months; 95% CI, 16.2-29.3). Many infants (61%) were exclusively breastfed for less than 5.5 months and 16% (95% CI, 10.9-22.0) were exclusively breastfed for more than 6.5 months. Families receiving income support were less likely to discontinue exclusive breastfeeding before 5.5 months (pOR1- < 5.5 months = 0.34; 95% CI, 0.13, 0.85) relative to those not receiving income support, in adjusted models. No other measured factors were significantly related to exclusive breastfeeding duration. Conclusions: The majority of Inuit Canadian infants receive suboptimal exclusive breastfeeding. National, provincial, and community-specific interventions to protect, promote, and support exclusive breastfeeding should emphasize not only the benefits of exclusively breastfeeding to 6 months but also the importance of timely introduction of complementary foods into the infant's diet.